Cyber Security Applied For Financial Sector In Indonesia - Machfud Sidik (LPPM-STPI, 2020)
This paper examines the supervisory issues underlying the potential developments and risks in cyber security applied to the financial industry. Cyber ??attacks on financial institutions and financial market infrastructure are becoming more widespread and more sophisticated. Cybercrime is a growing threat in the virtual world as individuals and financial sector organizations rely more and more on the internet at an increasing pace. Awareness of cybercrime risks has increased, companies are actively managing cyber risks and investing in cyber security, and to some extent transferring and pooling their risks through cyber liability insurance policies. International experience shows that the financial sector can develop an effective electronic transaction security framework through the latest methods to maintain public trust and financial stability by implementing policies: (i) a clear legal regime; (ii) proportionate action to prevent financial integrity risks; (iii) contingency plans for operational disruptions; (iv) risk control and access criteria in cyber systems; and (v) cross-disciplinary and holistic cybersecurity research is needed to address unexpected new challenges. Such steps are very important for financial institutions where the diffusion and collaboration while maintaining the confidentiality of the data held by each organization is a wider demand.